1999
DOI: 10.1088/0031-9155/44/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Plastic scintillator response to low-energy photons

Abstract: The plastic scintillator (PS) is a promising dosimeter for brachytherapy and other low-energy photon applications because of its high sensitivity and approximate tissue equivalence. As part of our project to develop a new PS material which maximizes sensitivity and radiological equivalence to water, we have measured the response, epsilon (light output/unit air kerma), of PS to low-energy bremsstrahlung (20 to 57 keV average energies) x-rays as well as photons emitted by 99mTc, 192Ir, and 137Cs sources, all of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 33 publications
6
81
0
Order By: Relevance
“…Other authors declare an energy dependence of plastic scintillator detectors sensitivity in the radiologic energy range (25-150 kVp). 13,14,[16][17][18][19] As reported by Williamson et al, 16 Lessard et al, 18 and Peralta and Rêgo, 19 it is partly related to energy absorption differences between the reference dose medium and the scintillator medium (air and polystyrene respectively in our case). As shown in Figure 4, the polystyrene-toair mass energy-absorption coefficients ratio shows significant variations ,100 keV.…”
Section: Full Paper: Scintillating Fibre Detector For Small Animal Dosupporting
confidence: 69%
See 4 more Smart Citations
“…Other authors declare an energy dependence of plastic scintillator detectors sensitivity in the radiologic energy range (25-150 kVp). 13,14,[16][17][18][19] As reported by Williamson et al, 16 Lessard et al, 18 and Peralta and Rêgo, 19 it is partly related to energy absorption differences between the reference dose medium and the scintillator medium (air and polystyrene respectively in our case). As shown in Figure 4, the polystyrene-toair mass energy-absorption coefficients ratio shows significant variations ,100 keV.…”
Section: Full Paper: Scintillating Fibre Detector For Small Animal Dosupporting
confidence: 69%
“…This energy dependence of plastic scintillator has first been expressed by Williamson et al 16 who showed a reduction of the scintillation light output with decreasing energy for photons ,133 keV. Other authors declare an energy dependence of plastic scintillator detectors sensitivity in the radiologic energy range (25-150 kVp).…”
Section: Full Paper: Scintillating Fibre Detector For Small Animal Domentioning
confidence: 79%
See 3 more Smart Citations